2020
DOI: 10.1136/bmjopen-2019-034612
|View full text |Cite
|
Sign up to set email alerts
|

Does Gleason score of positive surgical margin after radical prostatectomy affect biochemical recurrence and oncological outcomes? Protocol for systematic review

Abstract: IntroductionPositive surgical margins (PSM) in cancer patients are commonly associated with worse prognosis and a higher risk of secondary treatment. However, the relevance of this parameter in prostate cancer patients undergoing radical prostatectomy (RP) remains controversial, given the inconsistencies in its ability to predict biochemical recurrence (BCR) and oncological outcomes. Hence, further assessment of the utility of surgical margins for prostate cancer prognosis is required to predict these outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The usefulness of PSA and the Gleason score has been widely validated as pre-treatment prognostic markers [19]. In addition to these factors, other authors have highlighted how positive surgical margins after RP are in predicting the risk of biochemical recurrence and estimate oncological targets [47]. Although clinical staging has been found to be a good independent estimator of disease progression, there is a tendency to underestimate the final pathological stage at diagnosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of PSA and the Gleason score has been widely validated as pre-treatment prognostic markers [19]. In addition to these factors, other authors have highlighted how positive surgical margins after RP are in predicting the risk of biochemical recurrence and estimate oncological targets [47]. Although clinical staging has been found to be a good independent estimator of disease progression, there is a tendency to underestimate the final pathological stage at diagnosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Given the change in Gleason reporting in 2005 based on the ISUP Consensus Conference guidelines, the review only included studies published between 1 January 2005 and 31 October 2019 [13]. The search period was expanded by 1 month compared to the initial protocol published to include additional publications [14]. A further comprehensive literature search was also performed by examining the reference lists of included studies identified from the search.…”
Section: Methodsmentioning
confidence: 99%
“…A further comprehensive literature search was also performed by examining the reference lists of included studies identified from the search. The protocol was registered with the International Prospective Register of Systematic Reviews Database (CRD42019131800) and published [14]. Search terms were identified and adjusted to match the requirements of each database with the assistance of a librarian (Table S1).…”
Section: Methodsmentioning
confidence: 99%